Principles Behind Semantic Relation between Common Abbreviations and their Expansions on Instagram - Hasjim, Munirah; Arafah, Burhanuddin; Kaharuddin; Verlin, Sri; Aziz Genisa, Risma Asriani (International Journal of Criminology and Sociology, 2022)
The phenomenon of abbreviation used on Instagram is an interesting thing since the users modify the abbreviation form of expansion words making deviation from the original meaning. The principle of meaning relation between abbreviations and their expansions is used to make a change to the purposes of Instagram users. This research was aimed to describe the principle of abbreviation used in Instagram. An exploitation method was used by the technique of making screenshots and recording the abbreviation data. The results of research indicate that the principle of abbreviation consists of three forms namely inclusion, contact, and complementary. The results of this research can be very effective in understanding as well as how to use abbreviations, especially on Instagram. The Novelty of the study is in investigating the abbreviation used in Instagram.